Tricks & Illusions (Suffolk, UK Top That! Publishing, 2013)
Step-by-step instructions for world-famous magic tricks! From predicting colours to making a wand vanish, this ultimate guide to tricks and illusions will teach you the sleight-of-hand that you need to perform show-stopping magic!
Arts (Games)
2
Keywords: Games